Copper(II) import and reduction are dependent on His-Met clusters in the extracellular amino terminus of human copper transporter-1 - Kar, Sumanta; Sen, Samarpita; Maji, Saptarshi; Saraf, Deepashri; Ruturaj; Paul, Rupam; Dutt, Sohini; Mondal, Basudeb; Rodriguez-Boulan, Enrique; Schreiner, Ryan; Sengupta, Durba; Gupta, Arnab (Journal of Biological Chemistry, 2022)
Copper(I) is an essential metal for all life forms. Though Cu(II) is the most abundant and stable state, its reduction to Cu(I) via an unclear mechanism is prerequisite for its bioutilization. In eukaryotes, the copper transporter-1(CTR1) is the primary high-affinity copper importer, although its mechanism and role in Cu(II) reduction remain uncharacterized. Here we show that extracellular amino-terminus of human CTR1 contains two methionine-histidine clusters and neighboring aspartates that distinctly bind Cu(I) and Cu(II) preceding its import. We determined that hCTR1 localizes at the basolateral membrane of polarized MDCK-II cells and that its endocytosis to Common-Recycling-Endosomes is regulated by reduction of Cu(II) to Cu(I) and subsequent Cu(I) coordination by the methionine cluster. We demonstrate the transient binding of both Cu(II) and Cu(I) during the reduction process is facilitated by aspartates that also act as another crucial determinant of hCTR1 endocytosis. Mutating the first Methionine cluster ((7)Met-Gly-Met(9)) and Asp(13)( )abrogated copper uptake and endocytosis upon copper treatment. This phenotype could be reverted by treating the cells with reduced and nonreoxidizable Cu(I). We show that histidine clusters, on other hand, bind Cu(II) and are crucial for hCTR1 functioning at limiting copper. Finally, we show that two N-terminal His-Met-Asp clusters exhibit functional complementarity, as the second cluster is sufficient to preserve copper-induced CTR1 endocytosis upon complete deletion of the first cluster. We propose a novel and detailed mechanism by which the two His-Met-Asp residues of hCTR1 amino-terminus not only bind copper, but also maintain its reduced state, crucial for intracellular uptake.

Noncanonical regulation of the plasma membrane copper transporter CTRL through modulation of membrane mechanical properties - Chatterjee, Subhendu K.; Kar, Sumanta; Nikte, V, Siddhanta; Dash, Tisha; Ghosh, Tanmoy; Paul, Mrittika; Maji, Saptarshi; Sengupta, Durba; Sinha, Bidisha; Gupta, Arnab (Molecular Biology of the Cell, 2026)
We describe a noncanonical, membrane receptor-like regulation of the human copper transporter-1 (CTR1) in response to copper stimuli. CTR1 is the sole high-affinity trimeric plasma-membrane copper-importing channel that self-regulates by undergoing endocytosis to limit copper uptake. We observed that preceding copper-induced endocytosis, CTR1 forms clusters on the plasma membrane, a phenomenon that is typically observed in membrane receptors. We deciphered the mechanism of CTR1 clustering and studied its ramifications on the physical properties of plasma membranes harboring these clusters that could favor endocytosis. Membrane tension and fluctuation are fundamental regulators of pre-and post-endocytic events. Using coarse-grain molecular dynamics (MD)-simulations and coupled interference reflection microscopy-total internal reflection fluorescence microscopy (TIRF) we demonstrated that CTR1 clusters induce positive membrane curvature, an increase in local membrane tension, and a decrease in local membrane fluctuation; alterations that favor the formation of endocytic pits. Clustering is facilitated by copper sequestering methionine-rich extracellular amino-terminus of CTR1. MD-simulations and IRM-TIRF imaging revealed that CTR1 clustering is facilitated by membrane cholesterol, depletion of which delays CTR1 endocytosis. CTR1 clustering promotes clathrin-coated pit formation that engages recruitment of adaptor protein AP-2. To summarize, we report hitherto unknown ``pre-endocytic'' ``receptor-like'' phenomenon of ligand-induced clustering of a metal channel, which in turn regulates self-endocytosis by modulating membrane properties.